2021
DOI: 10.17510/wacana.v22i2.721
|View full text |Cite
|
Sign up to set email alerts
|

Language use and tourism in Yogyakarta; The linguistic landscape of Malioboro

Abstract: The present study provides a depiction of Malioboro through the interconnected prisms of language presentation, language preferences, and sign informativeness. Seven hundred and twenty-nine public signs were examined and analysed. Although the analysis was limited to words, the survey also paid attention to language preferences and sign informativeness, wit, clarity, and visibility to both local and foreign visitors. Our findings reveal the dominance of Indonesian in the linguistic landscape (LL) of Malioboro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…In the context of Indonesia, few LL studies have been conducted reporting the coexistences of languages and the profile of their visibility and salience in different settings e.g. education setting (Andriyanti, 2019), and tourism setting (Da Silva, Tjung, Wijayanti & Suwartono, 2021). Considering the magnitude of the tourism industry in Bali, the multilingual practices as reflected on the LL panorama in Bali tourism peripheries are expected to be super diverse.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Indonesia, few LL studies have been conducted reporting the coexistences of languages and the profile of their visibility and salience in different settings e.g. education setting (Andriyanti, 2019), and tourism setting (Da Silva, Tjung, Wijayanti & Suwartono, 2021). Considering the magnitude of the tourism industry in Bali, the multilingual practices as reflected on the LL panorama in Bali tourism peripheries are expected to be super diverse.…”
Section: Introductionmentioning
confidence: 99%
“…This choice reflects certain symbolism or values that try to be constructed by the shop owners. A study by da Silva et al (2021) argue that Bahasa Indonesia domination in Malioboro, Yogyakarta was motivated by the rooted national language policy and the expected readership. This was backgrounded by the fact that Malioboro location was visited more by domestic tourists.…”
Section: Discussionmentioning
confidence: 99%
“…This accentuated the use of English to construct certain symbolisms for the benefits of the business owners as in constructing 'up to date' and 'cosmopolitan' impressions for its readers. Da Silva et al (2021) examined the LL of both government and commercial signs in Malioboro, Yogyakarta, reporting that Bahasa Indonesia was the one dominating the LL panorama due its rooted compliance to the national language policy and its consideration of Indonesian as the main target of readership. The very few studies reported in the area of LL in Indonesia motivate this study to fill this gap.…”
Section: English On Public Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of linguistics landscape have been published around the world; some of them are conducted in Istanbul (Inal et al, 2020), Botswana (Akindele, 2011), Japan (Bayne, 2018), Italy (Vermeulen, 2019), Los Angeles (Chun, 2014), Canada (Dressler, 2015), Texas (Hult, 2014), Singapore (Tang, 2018), Philadelphia (Leung and Wu, 2012), and Philippines (Ellaga and Valdez, 2020) and Indonesia (Andriyanti, However, despite a large body of research on linguistics landscape in the last ten years, the extensive researches on linguistics landscape have thus far centered mostly on certain aspects like education ( Sayer, 2010;Rowland, 2013;Andriyanti, 2019;Sinaga et al, 2020), literacy practice (Leung & Wu, 2012, Poveda, 2012; bilingualism (Hulf, 2014, Dressler, 2015; multilingualism (Gorter, 2013); tourism spot (Widiyanto, 2019;Nirmala, 2019;Solikhah et al, 2020;da Silva et al, 2021), Urban planning ( Malinowski, 2016); and public services (Purnanto and Ardhian, 2020; Ardhian et al, 2021) to mention but a few. So far the researchers have concerned, the linguistics landscape related to culinary in Indonesia has been studied by several researchers (Pamuji and Khristianto, 2018;.…”
mentioning
confidence: 99%